2021
DOI: 10.3389/fpsyt.2021.679272
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Group Cognitive Behavioral Therapy Approach to Adult Non-rapid Eye Movement Parasomnias

Abstract: Background: Following the success of Cognitive Behavioral Therapy (CBT) for insomnia, there has been a growing recognition that similar treatment approaches might be equally beneficial for other major sleep disorders, including non-rapid eye movement (NREM) parasomnias. We have developed a novel, group-based, CBT-program for NREM parasomnias (CBT-NREMP), with the primary aim of reducing NREM parasomnia severity with relatively few treatment sessions.Methods: We investigated the effectiveness of CBT-NREMP in 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(53 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“… 89 Non-pharmacological techniques, like digital Cognitive Behavioral Therapy for Insomnia (dCBT-I) have been successful during lockdown, improving insomnia measures and daytime function. 90 Further validation of the provision of these therapeutic modalities, including digital therapeutics, and an expansion to other sleep disorders, 91 is now urgently required in order to stem the tsunami of lockdown-associated sleep difficulties and its consequences. Future clinical trials are similarly needed to clarify the optimal treatment strategies for sleep and other potentially long-term neuropsychiatric impacts of COVID-19.…”
Section: Conclusion and Suggestions For Post-covid Sleep Disorder’s Clinical Infrastructurementioning
confidence: 99%
“… 89 Non-pharmacological techniques, like digital Cognitive Behavioral Therapy for Insomnia (dCBT-I) have been successful during lockdown, improving insomnia measures and daytime function. 90 Further validation of the provision of these therapeutic modalities, including digital therapeutics, and an expansion to other sleep disorders, 91 is now urgently required in order to stem the tsunami of lockdown-associated sleep difficulties and its consequences. Future clinical trials are similarly needed to clarify the optimal treatment strategies for sleep and other potentially long-term neuropsychiatric impacts of COVID-19.…”
Section: Conclusion and Suggestions For Post-covid Sleep Disorder’s Clinical Infrastructurementioning
confidence: 99%
“…As up to a third of patients with NREM parasomnias display evidence of concomitant sleep pathology [20,40], such as OSA or PLMS, treatment of underlying sleep disorders alone, in particular OSA, can lead to satisfactory control of parasomnias in almost 20% of cases [20]. A novel non-pharmacological therapy, termed cognitive behavioural therapy (CBT) for NREM parasomnias, aimed at education of patients around disease pathophysiology and managing treatment expectations, combining sleep hygiene, anxiety management and mindfulness has offered promising results in select cases with behaviourally and psychologically driven precipitating and priming factors [50]. There is some early retrospective evidence to suggest that a combined non-pharmacological approach with sleep hygiene, safety measures, CBT and treatment for OSA if needed can be successful in up to a third of patients with NREM parasomnias, and this may be the preferred approach during pregnancy and in children [20].…”
Section: Nrem Parasomniasmentioning
confidence: 99%
“…The same year, a study on 46 NREM sleep parasomnia patients assessed the effect of a 5-session program (CBT-NREMP) that covered psychoeducation on DoA precipitating and priming factors; sleep hygiene and sleep behavioral techniques (sleep rescheduling to optimize homeostatic regulation, stimulus control to re-establish an association between the bed/bedroom and sleep); body-based relaxation techniques (mindfulness-based body scan, progressive muscle relaxation); and cognitive strategies to manage anxiety at night. The authors found a significant, although small, effect on the severity (but not the frequency) of parasomnia symptoms, sleep quality and anxiety/depressive symptoms [ 151 ]. More recently, a randomized controlled trial on a CBT protocol specifically developed for parasomnias (CBTp) produced statistically significant improvements in parasomnia frequency, severity, as well as in sleep continuity [ 152 ].…”
Section: Diagnosis Of Doamentioning
confidence: 99%